Poly[(μ(3)-benzene-1,3-dicarboxylato-κ(4) O (1):O (1′):O (3),O (3′))bis(pyridine-κN)cobalt(II)] - Xie, Fengxia (International Union of Crystallography, 2012)
In the asymmetric unit of the title polymeric compound, [Co(C(8)H(4)O(4))(C(5)H(5)N)(2)](n), there are two crystallographically independent Co(II) atoms, each of which is six-coordinated in a distorted octahedral geometry by four O atoms from benzenedicarboxylate anions and two N atoms from pyridine ligands. The benzenedicarboxylate dianions bridge the Co(II) atoms into a tape running along the b axis. C—H⋯O hydrogen bonds are observed in the tape and between the tapes.